Photo-induced effects in (Ag₃AsS₃)₀.₆(As₂S₃)₀.₄ thin films and multilayers with gold nanoparticles - Neimet, Yu.Yu.; Studenyak, I.P.; Buchuk, M.Yu.; Bohdan, R.; Kökényesi, S.; Daróci, L.; Nemec, P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
(Ag₃AsS₃)₀.₆(As₂S₃)₀.₄ single layer thin films, as well as ones deposited onto glass substrates previously covered with gold nanoparticle (GNP) layers were studied. Conventional thermal evaporation and pulse laser deposition techniques were used to deposit chalcogenide films onto previously prepared GNP layer. Roughness analysis of as-deposited film surfaces was performed. The influence of laser (LI) and e-beam (EBI) irradiation on structural and optical properties was analysed. Single layer films as well as sandwich structures with GNP on their base were found to be sensitive to LI and EBI. Irradiations caused growth of additional structures at films surfaces which was enhanced by a presence of gold.